Factors influences tourist’s waste reduction behavior while traveling - Fenitra, Rakotoarisoa Maminirina; Gunawan, Sri (International Journal of Psychosocial Rehabilitation, 2020)
Propose: This paper assesed to shed a light and give an extending understanding tourist waste reduction behavior and identifying the factors and its influence on intention to reduce waste. Data were collected through survey questionnaires with convience sampling method sampling. The data collected from 265 domestic tourist and international tourist visiting Bali, Indonesia and analyzed with multiple regression analysis to examine the relationship between personal norm, altruistic value, destination, green image, and attitude and intention behavior toward waste reduction. The study found that personal norm, altruistic value, destination, green image are associated the tourist attitude toward pro-environmental behavior and personal norm have a direct and indirect relationship on the intention to reduce waste through Attitude. Although, we found that altruistic value, destination green image has a positive influence on Attitude, these variables are has no significant relationship with behavior intention toward waste reduction. In addition, this study revealed that the type of tourist does not moderate the tourist pro- environmental behavior. This study empirically described that there is no different between both international and domestic tourist in pro-environmental behavior while traveling. This research provides an extending knowledge to the literature in the field of pro-environmental tourist behaviors. This result could be assets for other researcher with the similar interest and address the issues. The findings would hold implications for policymaker, as well as tourism and travel agency, tourism destination researchers and practitioners.